Adapting Pelintau Pencak Silat Teaching in Non-Formal Education During Early Recovery After a Flash Flood - Johaidah Mistar; Muhammad Sulfa; Myrza Akbari; Prista Cindi Navera; Madhan Anis (Sakura Digital Nusantara, 2026)
Background: A late-2025 flash flood disrupted the physical, social, and psychological foundations of Pelintau Pencak Silat learning in Aceh Tamiang, Indonesia. Objective: This study examined disaster impacts, instructors’ adaptive teaching strategies, and a provisional framework for disaster-responsive Pencak Silat teaching. Method: An intrinsic qualitative case study was conducted from January to March 2026. Seven purposively selected participants two lead instructors, two junior coaches, and three athletes completed 45–90-minute interviews; four training sessions were observed; and photographs, attendance records, and community archives were reviewed. Results: Interview evidence described loss of the training venue and cultural materials, dispersal, interrupted participation, and anxiety. Curriculum changes were supported mainly by lead-instructor accounts; method changes by junior-coach and athlete accounts; and organizational changes by instructor, coach, and athlete accounts. Observation and documentary materials contextualized the case, but the available record did not preserve item-level links that independently confirm particular interview claims. Cross-theme synthesis produced an interpretive pathway from disruption, through curriculum, method, and organizational adaptation and the relational mechanisms of safety, reconnection, identity, and autonomy, to participant-perceived early-recovery contributions. Conclusion: Pelintau instruction functioned as a flexible cultural learning space during early recovery. The framework is provisional rather than causal and requires stronger data-source traceability, longitudinal follow-up, and cross-site validation.